Strategic assessment of research priorities for sweetpotato. - Hareau, Guy; Kleinwechter, U.; Pradel, W.; Suarez, V.; Okello, J.J.; Vikraman, S. (CGIAR Research Program on Roots, Tubers and Bananas, 2014)
The following report presents an ex‐ante evaluation of priority research options for sweetpotato carried out in the scope of the strategic assessment of research priorities for the CGIAR Research Program on Roots, Tubers, and Bananas (RTB). It contains the results from the economic surplus model used for the assessment, which are extended to include estimations of the number of beneficiaries and poverty reduction effects. The report identifies and describes the sweetpotato research options taken into consideration for and included into the assessment. The socioeconomic and technological parameters used as input data for the analysis are described and information on the elicitation process and data sources is provided. Results are presented so as to explain the outputs obtained and interpreted with respect to the relevant differences between research options